Incretin enhancing and antihyperglycemic effect of curcuma longa, ocimum sanctum and trigonella foenum graecum on albino rat - S.D.INBARAJ,; M.MUNIAPPAN, (International Journal of Pharma and Bio Sciences, 2019)
This study carried out to investigate the incretin enhancing and antihyperglycemic effect of Curcuma longa, Ocimum sanctum and Trigonella foenum graecum extracts on albino rat. Methanolic leaf extract of Ocimum sanctum, Curcuma longa (Curcuma longa rhizomes ethyl acetate extract), methanolic seed extract of Fenugreek (Trigonella Foenum graecum) is prepared and supplied by Sami labs, Bangalore on request. After animal ethical clearance, Male albino rats (155–215 g) were divided into 8 groups each having 6 albino rats and randomly assigned Placebo( Normal saline) control group , Standard (Vildagliptin 50 mg/kg) group , low and high doses of all the three extracts. The baseline biochemical evaluation such as fasting blood glucose, Insulin level, Glucagon level, GLP-1 level, GIP level were measured before the experiment for all the above groups. After overnight fasting placebo, Vildagliptin and the extracts were orally administered by using rat feeding tube. 30 minutes later oral GTT was done. Blood samples were evaluated for blood sugar, Insulin, Glucagon, GLP-1, GIP at 0, 15, 45 minutes after oral glucose load. Trigonella Foenum graecum (2gm/kg) showed significant reduction in blood glucose (p= <0.001) and Ocimum sanctum (400 mg/kg) (p= < 0.05) at 45 minutes when compared to control. Ocimum sanctum (200 mg/kg & 400 mg/kg), Curcuma longa (200 mg/kg & 400 mg/kg) and Trigonella Foenum graecum (1gm/kg & 2gm/kg) showed significant (p=<0.001) increase in GIP levels at 45 minutes of OGTT. Curcuma longa (400 mg/kg) showed increase in Insulin level (p=0.001) at 45 minutes of OGTT. Trigonella Foenum graecum (1g/kg) showed reduction in glucagon levels (p=< 0.001) at 15 minutes. At 45 minutes Trigonella Foenum graecum 1g/kg and Curcuma longa (400 mg/kg) showed reduction in glucagon levels (p=<0.05). The extracts showed significant incretin enhancing and antihyperglycemic effects. Further clinical studies are necessary to establish the therapeutic potential of these extracts in the treatment of type 2 diabetes mellitus.